(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article provides information on the important role of pragmalinguistic and cognitive features of oral speech in the formation of effective communication and the fact that pragmalinguistic features include various elements of language use under the influence of the context and the speaker’s communicative goals